PENTINGNYA HOUSEKEEPING BAGI SUATU HOTEL - Parsidi, Parsidi (Sekolah Tinggi Pariwisata AMPTA, 2004)
The general public tends to think of Housekeeping as the Department that : makes the head, empties the asthray and waste basked, tidies up the bathroom and leaves fresh towels. The truth of the matter is of course that it takes more manpower to accomplish. Housekeeping's almost countless function than those of any ather Department in the lodging industry. Housekeeping's responsibility may begin with fabrics, and progress to the selection and purchase of all furniture and furnishings; it encompasses not only their cleaning but their maintenance, repair, refurbishment and eventual replacement. Areas of concern include : sleeping rooms, meeting rooms, halls andelevator, all considered